Software engineering for resilient systems : 8th International Workshop, SERENE 2016, Gothenburg, Sweden, September 5-6, 2016, Proceedings /: 8th International Workshop, SERENE 2016, Gothenburg, Sweden, September 5-6, 2016, Proceedings. (2016) - Unknown
No abstract available